2020
DOI: 10.1016/j.strueco.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Access to finance among small and medium-sized enterprises and job creation in Africa

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…The findings of the study showed that age (RQ2) was positively related to sales volume of these women entrepreneurs. Age and experience are relevant because younger businesswomen might be at a disadvantage in borrowing financial capital (Brixiov a et al, 2020). Older women have greater access to financial capital and markets than younger women entrepreneurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study showed that age (RQ2) was positively related to sales volume of these women entrepreneurs. Age and experience are relevant because younger businesswomen might be at a disadvantage in borrowing financial capital (Brixiov a et al, 2020). Older women have greater access to financial capital and markets than younger women entrepreneurs.…”
Section: Discussionmentioning
confidence: 99%
“…Women's engagement in these businesses has differential effects. The socio-economic characteristics of age, homeownership, family support and nature of the business also influence the sales volume/business performance (Brixiov a et al, 2020;OECD, 2020). Women informal entrepreneurs contribute to their families while facing economic downturns, while also facing the dual burden of caring for family and household work in addition to their businesses (Chant, 2014), thereby increasing possible work-family conflicts (Greenhaus and Beutell, 1985).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Agricultural cooperatives play an important role in many national economies, and they create many employment opportunities in Africa and worldwide. Cooperatives have a comparative advantage in terms of job creation over other types of businesses because they are labor-intensive by nature, they are cost-effective due to member commitment and participation which makes job creation sustainable (Brixiová, Kangoye and Yogo, 2020). Consequently, the commitment and participation of cooperative members encourage agricultural cooperatives to be an excellent tool for increasing agricultural production through new agricultural skills development and market accessibility (Mwadzingeni et al, 2020).…”
Section: Agricultural Cooperatives In a Global And African Contextmentioning
confidence: 99%
“…The author shows that small enterprises with access to formal funding generate additional jobs than companies without access, with employment in companies with more affordable and bigger loans increasing the quickest. The effects of finance access for production companies are greater than for services and are indicative of sectoral finance targeting as a possible industrialization policy (Brixiová et al, 2020). Cravo analyses and summarises 40 meticulous assessments of small and medium enterprises assistance services and provides proof to inform policy debates on small and medium-sized enterprises and corporate support.…”
Section: Review Of Literaturementioning
confidence: 99%